Rozkład procesu skumulowanych świadczeń w indywidualnym wieloopcyjnym ubezpieczeniu na życie - Homa, Magdalena (Distribution Function of Accumulated Payments in Individual Multi-State Life Insurance, 2006)
In the literature the methods of analyzing and pricing in traditional life insurance are described. But in practice the traditional life insurance respects only the basic insurance products, which in reality are more complicated. This determined the fact that I consider in my article a multi-state insurance policies, which are more attractive and better adopted to the needs of clients. With the life insurance and in particular multi-state insurance is connected the analysis of the following stochastic processes: loss or income of the insurer, total payments stream and accumulated expenses. Therefore, the essence of my work is the discussion on the form and distribution of total accumulated payments in multi-state insurance. I presented the form and recursion formula for distribution function of total payments in individual multi-state insurance, which determines essential measure of financial activity of the insurer. Knowledge of this process permits to describe and estimate the "riskness" of an individual contract. This is also the basis for further analysis of the insurance portfolio.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1108, s. 352-368